Thymic hyperplasia after autologous hematopoietic stem cell transplantation in multiple sclerosis: a case series - Mariottini, Alice; Boncompagni, Riccardo; Cozzi, Diletta; Simonetti, Edoardo; Repice, Anna Maria; Damato, Valentina; Giordano, Mirella; Miele, Vittorio; Nozzoli, Chiara; Massacesi, Luca (Frontiers in Immunology, 2024)
IntroductionReactivation of thymopoiesis in adult patients with autoimmune disorders treated with autologous haematopoietic stem cell transplantation (AHSCT) is supported by studies exploring immunoreconstitution. Radiological evidence of thymic hyperplasia after AHSCT was previously reported in patients with systemic sclerosis, but, to our knowledge, it has not been described in multiple sclerosis (MS), where premature thymic involution has been observed and immunosenescence might be accelerated by disease-modifying treatments (DMTs).Participants and methodsmonocentric case series including MS patients who performed a chest CT scan for clinical purposes after having received AHSCT (BEAM/ATG regimen) for aggressive MS failing DMTs. Chest CT exams were reviewed by a thoracic radiologist: thymic hyperplasia was defined as a rounded mass in the thymic loggia with a density around 40 Hounsfield Units (HU) and thickness >1.3 cm.ResultsFifteen MS patients were included; the median time interval between AHSCT and chest CT scan was 2 (range 1-18) months. All the patients were free from new inflammatory events and DMTs over a median follow-up of 36 months (range 12-84) after AHSCT. Thymic hyperplasia was detected in 3/15 (20%) cases in an exam taken 1 to 3 months after AHSCT; all these patients were females, and aged 30 to 40 years. Lung infections and secondary autoimmunity were diagnosed in 5 and 1 cases, respectively, none of which showed thymic hyperplasia. No associations between thymic hyperplasia and clinical-demographic characteristics or post-AHSCT outcomes were observed.ConclusionsThymic hyperplasia was detected in 20% of MS patients recently treated with AHSCT. These results are consistent with previous immunological studies showing that AHSCT promotes thymus reactivation in MS patients, further supporting de-novo thymopoiesis as a cornerstone of immune reconstitution after AHSCT in this population.